Tuning local carbon active sites saturability of graphitic carbon nitride to boost CO2 electroreduction towards CH4. (July 2020) - Chen, Zhou; Gao, Min-Rui; Zhang, Ya-Qian; Duan, Nanqi; Fan, Tingting; Xiao, Jing; Zhang, Jiawei; Dong, Yunyun; Li, Jianhui; Yi, Xiaodong; Luo, Jing-Li
Abstract: New approach to activating carbon active sites to facilitate the electroconversion of CO2 through N-vacancy engineering is proposed and confirmed by the density functional theory calculations and experimental results. N-vacancy engineered graphitic C3 N4 (g-C3 N4 ) is identified as an efficient electrocatalyst to boost CH4 formation owing to the three-coordinating to two-coordinating transition of the carbon atoms that surround N vacancies. The defected g-C3 N4 (DCN) exhibits a 44% faradaic efficiency with a CH4 partial current density of 14.8 mA/cm 2 at −1.27 VRHE in 0.5 M KHCO3 electrolyte, exceeding all the reported carbon-based materials and even being comparative to Cu-based electrocatalysts. Creation of more unsaturated carbon atoms enables the harmonic energy overlap near band gap edge between DCN and *CO, accounting for an improved strength of *CO on DCN, a lower energy barrier and an enhanced CO2 RR to form CH4 . This strategy holds the promise for tuning atomic configuration to enhance activity of catalyst. Graphical abstract: We report the new strategy to tune the elelctronic structure of N-vacancy engineered g-C3 N4 and harmonize activation and adsorption energies between the key intermediate adsorbate (*CO) and catalysts for the electrocatalytic CO2 reduction to deep reduction product CH4 with high selectivity and partial current density. Image 1 Highlights: N2V -vacancy engineered g-C3 N4 is adapted as the electrocatalyst for CO2 RR to form CH4 for the first time. DFT calculation identifies N2V- vacancy engineered g-C3 N4 identified as an efficient electrocatalyst for CO2 RR to CH4 . Newly formed PDOS overlap intensifies the interaction between *CO and g-C3 N4 and facilitates *CO activation. N2V -vacancy engineered g-C3 N4 delivers a maximum FECH4 (44%) and partial current density of −14.8 mA/cm 2 at −1.27 VRHE. Enhanced adsorption of key intermediates on g-C3 N4 and lowered activation energy of RDS improve the activity of g-C3 N4 .